A Critique of the Historical Clinical Risk–20, Version 3, Risk Assessment Instrument. Issue 4 (7th August 2016) - Judges, Rachel; Egan, Vincent; Broad, Grant
ABSTRACT: The aim of this critique is to provide an overview of the Historical Clinical Risk–20, version 3, exploring its psychometric properties, considering its clinical and research applications, while also taking into account its use in forensic mental health settings. The HCR-20 is considered the most researched and best empirically guided risk assessment of violence, and it has been widely adopted. Version 3 of the instrument was introduced in 2013 and as such the evidence base for its reliability, validity, and clinical utility is still in its infancy. However, if it maintains the core principles of the HCR-20V2, it may prove itself a similarly reliable and valid assessment. Despite some limitations, the research to date is supportive, demonstrating high levels of internal and interrater reliability, and good levels of concurrent and predictive validity. Its clinical utility has also been supported.